Analisis Penerapan Good Corporate Governance Berbasis Etika Syariah Pada Bank Syariah: (Studi Kasus Bank Syariah Indonesia “KCP Sawangan Sari Plaza”) - Syauqi Habatulloh Azzakni; Ahmed Alkautsar Qurratu’ain (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2025)
The implementation of Good Corporate Governance (GCG) is a crucial foundation for maintaining public trust in Indonesia’s Islamic banking sector. Yet, the effectiveness of GCG is often debated because formal practices tend to be technocratic and procedural, lacking deeper internalization of Sharia Ethical values. This study analyzes the application of GCG based on Sharia Ethics at Bank Syariah Indonesia (BSI), with a case study at KCP Sawangan Sari Plaza. Using a qualitative approach and case study method, data were collected through source triangulation, including in-depth interviews with the Branch Operation and Service Manager (BOSM), customer service officers, and tellers. These interviews were supported by participatory observation and an examination of corporate documents. The findings reveal no significant discrepancy between formal GCG practices and Sharia Ethics at the research site. GCG principles such as Transparency, Accountability, Responsibility, and Fairness are consistently implemented and rooted in ethical values like Amanah (trustworthiness), Shidq (honesty), and ’Adl (justice). A key insight from this study is the shift in employee motivation from fear-based compliance toward value-based compliance. This shows that the integration of GCG and Sharia Ethics is strongly influenced by ethical leadership and the development of a spiritual work culture at the branch level.